Recovering the concept of availability in the psychological clinic - Bertella, Maria Adela (2021)
The theme of this work is to reflect on and recover the importance of the concept of availability as the axis of therapeutic work beyond the clinical model that frames therapy. Both classical authors and current studies linked to the genuine development of the person were used as reference sources. From the availability of the therapist towards the patient’s points of tension, the  patient will be able to identify with this attitude of accommodating in himself what is avoided, denied, rejected and ultimately perhaps he can treat himself in his difficulties as he feels it is treated or hosted by your therapist. That the person of the patient can get his life out of the stagnation that stops and limits it, and thus restart it, implies offering him availability and not forcing him to meet theoretical goals. Remove aspects of life from stagnation so that the water of development can continue its course towards its own truth, that of its unique singularity.